EVALUASI PEMANFAATAN FITUR SOBATDUKCAPIL PADA APLIKASI TANGERANG LIVE DALAM PELAYANAN PELAPORAN KEPENDUDUKAN DI KOTA TANGERANG TAHUN 2024 - Farah Mumtazah; Dewi Erowati (Journal of Politic and Government Studies, 2026)
Digital transformation in public services encourages local governments to provide integrated app-based services. The Tangerang City Government has developed the Tangerang LIVE Application, which includes the SobatDukcapil feature as an online platform for reporting population administration, particularly birth reports. This application was selected because Tangerang LIVE is a regional super app that integrates various public services and forms part of the 2024 digital service optimization efforts. The high ownership of electronic ID cards (KTP-el) in 2023, reaching 99.8%, along with the developing ecosystem of digital services, indicates a relatively advanced level of administrative readiness and infrastructure. This condition makes Tangerang City an attractive case for study, as it has a strong digital foundation, making the evaluation of app-based service utilization important to assess the consistency between system readiness and on-the-ground implementation. The research employs a qualitative method with a case study approach. Data collection was conducted using interviews, observations, and documentation. Data validity was tested using source triangulation techniques, by comparing information obtained from various informants, such as 5 application users, Disdukcapil employees, and application system managers. The data analysis process followed the Miles and Huberman model, encompassing data reduction, data presentation, and drawing conclusions. William N. Dunn's evaluation framework was used to analyze indicators of effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. The research findings indicate that the utilization of the Tangerang LIVE Application's SobatDukcapil feature is generally quite optimal. For several indicators, effectiveness and efficiency have facilitated reporting and saved time, but reporting targets have not been maximized because many people still prefer face-to face services. Feature adequacy and comprehensive guides are sufficient, but service 1 status notifications are not yet real-time. Technical equity is adequate with hybrid services, but it is hindered by low digital literacy among the elderly. Service responsiveness is quite good, but the passive notification system causes uncertainty. Service accuracy is highly optimal, supported by multi-layered verification, accelerated services, periodic system updates, and strengthened data security. This research recommends that the Tangerang City Government improve the service notification system to make it more informative and real-time, strengthen data security, and optimize digital service integration to encourage a more massive shift by the community to online services